Design and Analysis of Microstrip Patch Antenna for 6G Millimeter-Wave Communication - Ramineni, P.; Dharmapuri , Y. G. (Journal of Scientific Research, 2025)
The growing requirements of sixth-generation (6G) applications call for wireless communication systems, capable of delivering ultra-high speeds and substantial capacity, are critical for the successful implementation of 6G technology. To address this demand, a microstrip antenna was developed to operate within the 110 GHz to 120 GHz frequency range, with its performance meticulously evaluated using various patch materials, including copper. A comprehensive analysis of key antenna parameters was performed, leveraging Computer Simulation Technology (CST) Studio software for rigorous simulation and optimization tailored to 6G applications within this frequency spectrum. At 110 GHz, the proposed antenna exhibited exceptional performance metrics, including a directivity of 186.7 dB, a gain of 10.03 dBi, a radiation efficiency of 176.7 dB, a reflection coefficient of -12 dB, a total efficiency of -177 dB, and a voltage standing wave ratio (VSWR) between 1.5 and 2. At 120 GHz, similarly impressive results were achieved, with a directivity of 181.5 dB, a gain of 4.697 dBi, a radiation efficiency of -176.9 dB, a reflection coefficient ranging from -14 dB to -15 dB, a total efficiency of -177 dB, and a VSWR of 1.5. This research highlights the critical role of optimizing microstrip antenna designs for 6G millimeter-wave communication, offering valuable insights to propel advancements in next-generation wireless communication systems.